Brazilian and North-American nursing in the HOPE Project (1972): approximations and gaps - Djailson José Delgado Carlos; Maria Itayra Coelho de Souza Padilha
ABSTRACT Objective: Understand the structuring and operation of the Nursing Service on the hospital ship HOPE and the relations between Nursing from North America and from Rio Grande do Norte. Method: Qualitative, sociohistorical research, developed by consulting documentary and oral sources. Results: The analysis revealed the categories: The HOPE Project: impressions of its nurses and Nursing on the hospital ship SS HOPE: Brazilian impressions. These categories revealed a Nursing Service similar to that of a general hospital, ordered by scales and which functioned uninterruptedly in the three shifts. Final considerations: The Nursing Service consisted exclusively of nurses; followed a hierarchical system; with accumulation of administrative and care functions; strict, precise and technical execution of the work. The language and cultural barriers do not seem to have compromised the Exchange and the work system in counterparts.